2019
DOI: 10.3390/ijms20030764
|View full text |Cite
|
Sign up to set email alerts
|

Honey-Mediated Wound Healing: H2O2 Entry through AQP3 Determines Extracellular Ca2+ Influx

Abstract: Since Biblical times, honey has been utilized in “folk medicine”, and in recent decades the positive qualities of honey have been re-discovered and are gaining acceptance. Scientific literature states that honey has been successfully utilized on infections not responding to classic antiseptic and antibiotic therapy, because of its intrinsic H2O2 production. In our study, we demonstrated the involvement of H2O2 as a main mediator of honey regenerative effects on an immortalized human keratinocyte cell line. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 61 publications
4
57
0
Order By: Relevance
“…22 Notably, a recent study further observed activated TRPM2 in keratinocytes under oxidative stress. 23 Based on these findings, we hypothesize that oxidative stress can activate the NLRP3 inflammasome in keratinocytes through TRPM2, which enhances the cutaneous T-cell response in patients with vitiligo.…”
mentioning
confidence: 79%
“…22 Notably, a recent study further observed activated TRPM2 in keratinocytes under oxidative stress. 23 Based on these findings, we hypothesize that oxidative stress can activate the NLRP3 inflammasome in keratinocytes through TRPM2, which enhances the cutaneous T-cell response in patients with vitiligo.…”
mentioning
confidence: 79%
“…Honey induced extracellular Ca 2+ entry results in wound healing. It is similar to role plays by Ca 2+ signaling in tissue regeneration [47]. Moreover honey regulates the process of epithelial mesenchymal transition (EMT) and it has a positive impact on wound healing.…”
Section: Honeymentioning
confidence: 69%
“…It has, therefore, been suggested that optical stimulation of P3HT polymer induces the production of singlets and charge states, which in turn reduce oxygen dissolved in the medium to form superperoxide. Furthermore, superperoxide leads to the generation of hydrogen peroxide (H 2 O 2 ), which can permeate the plasma membrane through specific aquaporins (e.g., aquaporin 3) and thereby activate TRPV1 [44,207,217]. Overall, this work evidenced how the combined use of optical excitation and organic polymers technology can open interesting perspectives for the modulation of progenitor cells fate and, more generally, corroborated the idea that controlling the signaling pathways driving ECFC proliferation, differentiation, and tube formation may represent a reliable strategy to improve the regenerative outcome of therapeutic angiogenesis.…”
Section: Gene-less Opto-stimulation Of Trpv1 Leads To In Vitro Modulamentioning
confidence: 99%